Andrographolide, a diterpene lactone from Andrographis paniculata and its therapeutic promises in cancer. (28th April 2018) - Islam, Muhammad Torequl; Ali, Eunüs S.; Uddin, Shaikh Jamal; Islam, Md. Amirul; Shaw, Subrata; Khan, Ishaq N.; Saravi, Seyed Soheil Saeedi; Ahmad, Saheem; Rehman, Shahnawaz; Gupta, Vijai Kumar; Găman, Mihnea-Alexandru; Găman, Amelia Maria; et al.
Abstract: The diterpene lactone andrographolide, isolated from Andrographis paniculata, has been proven to possess several important protective biological activities, including antioxidant, anti-inflammatory, immunomodulatory, antiseptic, antimicrobial, cytotoxic, hypolipidemic, cardioprotective, hepatoprotective, and neuroprotective effects. In addition, it has been reported to play a therapeutic role in the treatment of major human diseases, such as Parkinson's disease, rheumatoid arthritis, and colitis. This systematic review aims to highlight andrographolide as a promising agent in cancer treatment. To this purpose, a number of databases were used to search for the cytotoxic/anticancer effects of andrographolide in pre-clinical and clinical studies. Among 1703 identified literature articles, 139 were included in this review; 109 were investigated as non-clinical, whereas 24, 3, and 3 were pre-clinical, clinical, and non-pre-clinical trials, respectively. Among the model systems, cultured cell lines appeared as the most frequently (79.14%) used, followed by in vivo models using rodents, among others. Furthermore, andrographolide was found to exert cytotoxic/anticancer effects on almost all types of cell lines with the underlying mechanisms involving oxidative stress, cell cycle arrest, anti-inflammatory and immune system mediated effects, apoptosis, necrosis, autophagy, inhibition of cell adhesion, proliferation, migration, invasion, anti-angiogenic activity, and other miscellaneous actions. After careful consideration of the relevant evidence, we suggest that andrographolide can be one of the potential agents in the treatment of cancer in the near future. Highlights: Andrographolide (diterpene lactone andrographolide, from Andrographis paniculata ) as a promising agent in cancer treatment. A number of databases were searched for pre-clinical and clinical trials on the anticancer effects of andrographolide. Among model systems, cultured cell lines appeared most frequently used followed by in vivo models using rodents. The various mechanisms by which this compound exerts its action are summarised. It is important to carry out toxicological studies prior to installing andrographolide into full-length clinical trials.